Effect of adding Spirulina platensis algae to small ruminant rations on productive, reproductive traits and some blood components - Mohamed Mohamed El-Deeb; Megahed Abdel-Gawad; Mohamed Ahmed Mohamed Abdel-Hafez; Fatma Elsayed Saba; Eid Mohamed Mohamed Ibrahim (Acta Scientiarum. Animal Sciences, 2022)
This experiment conducted using 20 Rahmani ewes at the last third of pregnancy in two equal groups. One group served as control, while the other group received Spirulina platensis (SP) at the rate of 0.5 gm 10 kg-1 live body weight. The objective was to find out the effect of adding Spirulina platensis algae to small ruminant rations on reproductive and productive traits and blood components of sheep. The experiments lasted for 120 days for both dams and their lambs after weaning. The findings proved that adding SP in ewes' diets had no effect on the average of live body weight change. Average milk yield was significantly (p <0.01) higher in the treatment group than the control. Lamb's birth weight and daily body gain of the treated group were significantly (p <0.01) higher than the control. Blood and serum picture profile of ewes were significantly higher when fed SP additive than the control. It could be concluded that the addition of SP to the ration of sheep positively preserved their health, productive and reproductive status as well as their lambs' growth rate. Also the additive improved the economic efficiency of treated animals by about 53.13%.